African human mtDNA phylogeography at-a-glance - Rosa, Alexandra (2011)
The mitochondrial DNA (mtDNA) genetic system has long proven to be useful for studying the demographic history of our species, since their proposed Southeast/East African origin 200 kya. Despite the weak archaeological and anthropologic records, which render a difficult understanding of early intra continental migrations, the phylogenetic L0-L1’6 split at about 140-160 kya is thought to represent also an early sub-structuring of small and isolated communities in South and East Africa. Regional variation accumulated over the following millennia, with L2 and L3 lineages arising in Central and East Africa 100-75 kya. Their sub-Saharan dispersal not later than 60 kya, largely overwhelmed the L0’1 distribution, nowadays limited to South African Khoisan and Central African Pygmies. Cyclic expansions and retractions of the equatorial forest between 40 kya and the “Last Glacial Aridity Maximum” were able to reduce the genetic diversity of modern humans.. Surviving regional-specific lineages have emerged from the Sahelian refuge areas, repopulating the region and contributing to the overall West African genetic similarity. Particular L1- L3 lineages mirror the substantial population growth made possible by moister and warmer conditions of the Sahara’s Wet Phase and the adoption of agriculture and iron smelting techniques. The diffusion of the farming expertise from a Central African source towards South Africa was mediated by the Bantu people 3 kya. The strong impact of their gene flow almost erased the pre-existent maternal pool. Non-L mtDNAs testify for Eurasian lineages that have enriched the African maternal pool at different timeframes: i) Near and Middle Eastern influences in Upper Palaeolithic, probably link to the spread of Afro-Asiatic languages; ii) particular lineages from West Eurasia around or after the glacial period; iii) post-glacial mtDNA signatures from the Franco-Cantabrian refugia, that have crossed the Strait of Gibraltar and iv) Eurasian lineages tracing back to the Neolithic or more recent historical episodes. Finally, the non-random sub-Saharan spread of North African lineages was likely mediated by the ancestors of Fulani, nomadic pastoral communities in the Sahel.